Long-term effects of physical activity prescription after bariatric surgery: A randomized controlled trial. (2nd November 2022) - Fagevik Olsén, Monika; Wiklund, Malin; Sandberg, Erica; Lundqvist, Stefan; Dean, Elizabeth
ABSTRACT: Purpose: This study examined the effects of physical activity prescription (PAP) in patients after gastric bypass surgery. Patients' physical activity (PA) levels and outcomes were followed over their first postoperative year. Methods: Patients slated for bariatric surgery were randomized to a control group (n = 64) (basic information about postoperative PA) or an intervention group (n = 57) (also received physical therapist-prescribed PAP). Outcome measures were self-reported PA/exercise and sedentary time; and weight, waist circumference, blood pressure, and blood lipids; recorded pre-operatively and at 2, 6, and 12 months postoperatively. Follow-ups were conducted by nurses/dieticians. Trial registration: "Research and Development in Sweden" number 107371. Results: There were no differences between the groups except for higher level of PA (579 vs. 182 minutes/week) six months after surgery ( p = .046) and a larger decrease in cholesterol (−24 vs. −8%) after a year ( p = .017) in the intervention group. Patients in both groups lost considerable weight, had reduced waist circumference, and increased PA ( p < .001). Conclusion: Although marked differences between groups were not observed over one year, the intervention group increased its PA 6-months postoperatively, but not at other time points. Whether long-term outcomes of PAP use are more robust with physical therapist participation across follow-ups warrants study.